How to Read a Historical Source through a Literary Lens? - Bering, Piotr (Przestrzenie Teorii, 2024)
The article presents some possibilities of using contemporary literary research methods for analyzing historical sources. However, in the analysis of literary work as a historical source, attempts at “reversed” reading (i.e. source as literature) are still insufficient. The article presents some research tools based on text theory, which could be adapted to reading historical sources. There are privileged texts with some aesthetic features. The above-mentioned methods could not be used directly to analyze historical sources; they should be completed with extra-textual data.